2011
DOI: 10.1128/jcm.01834-10
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of a Novel Pattern of Infections by Enteric Adenovirus Serotype 41 among Children below 5 Years of Age in Kolkata, India

Abstract: There is no significant variation in the sequences of hexon and fiber genes among strains from symptomatic and asymptomatic children. Our data confirm the circulation of an AdV-41 strain with a novel pattern in Kolkata, India, among children below 5 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
67
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 54 publications
17
67
5
1
Order By: Relevance
“…Overall, the HAdV‐positive rate was 5.5% (113/2064), which is lower than that found in a previous study (8.7%; 20/231) in Korea during 1998–1999 (33). Although earlier studies reported that the incidence of HAdV‐40 and HAdV‐41 infections in acute gastroenteritis is similar (34, 35), more recent studies have reported a predominance of HAdV‐41 (17, 29, 36, 37).…”
Section: Discussionmentioning
confidence: 94%
“…Overall, the HAdV‐positive rate was 5.5% (113/2064), which is lower than that found in a previous study (8.7%; 20/231) in Korea during 1998–1999 (33). Although earlier studies reported that the incidence of HAdV‐40 and HAdV‐41 infections in acute gastroenteritis is similar (34, 35), more recent studies have reported a predominance of HAdV‐41 (17, 29, 36, 37).…”
Section: Discussionmentioning
confidence: 94%
“…Types 40 and 41 are responsible for 1%-20% cases of diarrhoea in young children. Other species such as A (types 12, 18, and 31), C (types 1, 2, and 5) and D (types 28,29,30,32,37,[43][44][45][46] have also been associated with diarrhoea (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The probe and primers are shown in Supplementary Table 1b. The two positive samples were screened for common diarrhea viruses, including rotavirus group A, norovirus GI/GII, sapovirus, astrovirus, enteric adenovirus, enterovirus, and salivirus, using RT-PCR as described previously [16][17][18][19][20]. One of the two positive samples (ID GR-1113-59) was found positive for NoV GII and salivirus [20].…”
Section: Case Descriptionmentioning
confidence: 99%